Historical Existence and the Definition of Street Children in the Contexts of Malaysian Law: (Sejarah Kewujudan Golongan Kanak-Kanak Jalanan dan Definisi dalam Konteks Perundangan Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Historically, street children have been the result of rapid technological advances, leading to the migration of people from rural areas to big cities. However, due to several factors that thwart their efforts to improve their lives, street children come into being. To date, the issue of street children has still met a dead end. In addition to the problems they face in terms of economic, social and environmental aspects, the main drawback is the absence of a clear definition of 'street children' as it concerns various categories of children on the streets. The absence of a definitive definition not only hinders data collection and further information concerning this group but makes it challenging to help them. This paper discusses the history of street children, definitions by several authors, terms used to refer to 'street children' in Malaysia, an explanation of the Childrens' Act 2001 (Act 611) and issues that arise therefrom.Keywords: Street children, definition, Child Act 2001 (Act 611), human rights, discrimination